2017
DOI: 10.33094/7.2017.11.20.26
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Family Business in Malaysia

Abstract: Performance of family firms is an interestingly growing topic of study. In Malaysia, many studies were conducted in an attempt to understand performance of family firms, however these studies have been biased towards operationalizing performance through financial indicators particularly Tobin's Q. Researchers also tended to test the effect of various factors relating to corporate governance and board of directors on performance. Ethnic wise, performance of family firms may be significantly impacted by culture.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The effectiveness of supply chain management is entirely based on its capability of reducing cost, enhancing production flexibility, bringing innovation, strengthening the relation and satisfying the buyer (Banomyong & Supatn, 2011;Castorena et al, 2014;Purnama, 2014;Chielotam, 2015;Luna-Maldonado et al, 2016;Crainic & Laporte, 2016;Stevens & Johnson, 2016;Malarvizhi et al, 2018, Le et al, 2018. SCM is an organizational network, which connects each and every segment of organization and adds value at each and every step of strategic operations (Santhi and Gurunathan, 2014;Anyanwu et al, 2016;Jones & Mwakipsile, 2017;Mosbah et al, 2017;Kucukkocaoglu & Bozkurt, 2018;Maldonado-Guzman, et al, 2018). Crainic and Laporte (2016) argued that SCM is a coordinated set of activities staring from procurement to production and ends at consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of supply chain management is entirely based on its capability of reducing cost, enhancing production flexibility, bringing innovation, strengthening the relation and satisfying the buyer (Banomyong & Supatn, 2011;Castorena et al, 2014;Purnama, 2014;Chielotam, 2015;Luna-Maldonado et al, 2016;Crainic & Laporte, 2016;Stevens & Johnson, 2016;Malarvizhi et al, 2018, Le et al, 2018. SCM is an organizational network, which connects each and every segment of organization and adds value at each and every step of strategic operations (Santhi and Gurunathan, 2014;Anyanwu et al, 2016;Jones & Mwakipsile, 2017;Mosbah et al, 2017;Kucukkocaoglu & Bozkurt, 2018;Maldonado-Guzman, et al, 2018). Crainic and Laporte (2016) argued that SCM is a coordinated set of activities staring from procurement to production and ends at consumers.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of RBV indicates that through organizational resources and capabilities, business firms achieve the competitive advantage in the market (Peng et al, 2008;Anigbogu & Nduka, 2014;Santhi & Gurunathan, 2014;Anyanwu et al, 2016;Jones & Mwakipsile, 2017;Mosbah et al, 2017;Malarvizhi et al, 2018, Le et al, 2018. So, the indication of the SC can be viewed as both internal and external integrated capabilities that can directly impact the performance of the business firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, the executive with a greater control and large shareholdings are more concerned with their own self-interests than the interests of the shareholders at large. Mosbah, Serief and Kalsom Abd Wahab (2017) extend their the link with performance among the family business, they found that through financial indictors using a Tobin Q ratio reported the performance of family firms may be significantly influenced by their culture practices.…”
Section: Introductionmentioning
confidence: 98%
“…Examination on past literature,such as Abdul Rahman (2006) indicates that the main nature of Malaysia listed firms were owned by family business, although the history proved that since independence most of the Malaysian firms were controlled by foreign investors and the government. More ddiscussion on family business characteristics in Malaysia by Mosbah, Serief and Kalsom Abd Wahab (2017) found that several indicators could be used for their identification including business contributions to GDPs, firm size, business owned by ethnic and preference to follow culture and management style of the business founder. And the family culture may have a significant impact on family founding firm performance where the successful story of family founding firms find the roles of participation and ethnic networks governing the entrepreneurial practice.…”
Section: Introductionmentioning
confidence: 99%